Capital structure dynamics and financing decisions of Chinese listed companies - Zhao, Yuan (2019)
This study examines the capital structure dynamics and financing decisions of listed companies in the People’s Republic of China. A new dataset of 2048 Chinese listed companies for the period from 1990 to 2014 is used to investigate the determinants of capital structure in the dynamic framework. The difference and system Generalised Method of Moments (GMM) estimators are applied for the dynamic models to alleviate endogeneity concerns in corporate finance research. The costs of adjustment and speed of adjustment to the target capital structure are estimated, showing that the Chinese listed companies take partial adjustment towards their target leverage. The firm-specific factors that are expected to have an effect on the adjustment speed towards the optimum are analysed as well. The results indicate that larger firms tend to adjust faster to their targets. This study also proves that corporate governance mechanisms such as board independence, board size and ownership concentration can determine corporate capital structure while managerial shareholdings and CEO duality have no effect on financing decisions of Chinese listed firms. Additionally, the quantitative analysis is complemented by semi-structured interviews, which can provide valuable insights into the link between theory and practice.